PENGARUH PENGGUNAAN TEKNIK KRITIK PADA KEMAMPUAN MEMBUAT RESENSI NOVEL â€œSANG PEMIMPIâ€ SISWA KELAS XI SMA NEGERI 1 SIABU - Dahafni, Ely (Linguistik : Jurnal Bahasa dan Sastra, 2023)
The purpose of this study was to determine the effect of using critical techniques on the ability to write a review of the novel "Sang Pemimpi" for class XI students of SMA Negeri 1 Siabu. This research method uses quantitative methods with a descriptive approach. The population in this study were all 195 students of class XI at SMA Negeri 1 Siabu. The sample used in this study were 29 students of class XI IPA2 at SMA Negeri 1 Siabu, consisting of 9 males and 20 females. The sample was determined using a random sampling technique. The data collection technique uses a test in which this test uses 10 multiple choice questions and 1 filled-in question. The results of the study show the difference in the average value of the X and Y variables. The average value of the X variable is 72.41 "Good" while the value on the Y variable test results is 62.93 in the "Enough" category. After the data is analyzed, it can be stated that N = 29 with X = 2100, Y = 1825, X2 = 174600, Y2 = 132375, so XY = 143150. Then if you look at the average, it can be shown that X = 72.41, Y= 62.93 X2= 6020.69, Y2= 4564.66 XY = 4936.21. This is based on the hypothesis testing carried out on the data found, namely the hypothesis that the rxy value is 0.553 so that when compared to the r table (0.553 0.381), the hypothesis in this study is accepted.